Performance evaluation of basalt fiber reinforced mortar under freeze-thaw and chloride-rich environments - Guo, Yiming; Yokota, Hiroshi (Journal of Asian Concrete Federation, 2018)
Mixing short fibers is one of the effective methods to improve tensile properties and even durability of mortar and concrete. Basalt fiber is a new material that is purely made from basalt rocks. Comparing with traditional steel and synthetic fibers, basalt fiber is environmental-friendly, strong, corrosion-free, hightemperature resistant, and less expensive. Though some research have been carried out on the properties of basalt fiber reinforced cement and concrete, their durability against freezing-and-thawing and chloride ion penetration still remains unclear. In addition, the optimized fiber content and performance evaluation of basalt fiber reinforced mortar and concrete are not well defined. This paper deals with the durability of basalt fiber reinforced mortar under combined freeze-thaw and chloride-rich environments, and proposes the optimized fiber content and the mechanism of basalt fiber for enhancing the durability of mortar. As the results, basalt fibers significantly improve the durability of mortar. Compressive strength of basalt fiber reinforced mortar slightly increases when the fiber content is less than 0.1 vol.%. Bending strength of mortar increaseswith increase in fiber content. It was also found that basalt fibers improve resistance against chloride ion penetration of mortar.